2019
DOI: 10.5194/acp-19-10303-2019
|View full text |Cite
|
Sign up to set email alerts
|

Winter 2018 major sudden stratospheric warming impact on midlatitude mesosphere from microwave radiometer measurements

Abstract: The impact of a major sudden stratospheric warming (SSW) in the Arctic in February 2018 on the midlatitude mesosphere is investigated by performing the microwave radiometer measurements of carbon monoxide (CO) and zonal wind above Kharkiv, Ukraine (50.0 • N, 36.3 • E). The mesospheric peculiarities of this SSW event were observed using a recently designed and installed microwave radiometer in eastern Europe for the first time. Data from the ERA-Interim and MERRA-2 reanalyses, as well as the Aura microwave limb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 76 publications
7
63
0
Order By: Relevance
“…In Bern water vapour increased by 15 % (Flury et al, 2009), whereas at Seoul a water vapour decrease of 40 % was observed (De Wachter et al, 2011). The zonal wind reversals could be observed during several SSWs at midlatitudes and in the Arctic (Wang et al, 2019;Rüfenacht et al, 2014;Schranz et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In Bern water vapour increased by 15 % (Flury et al, 2009), whereas at Seoul a water vapour decrease of 40 % was observed (De Wachter et al, 2011). The zonal wind reversals could be observed during several SSWs at midlatitudes and in the Arctic (Wang et al, 2019;Rüfenacht et al, 2014;Schranz et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…For the period when primarily EOS-MLS data were assimilated in the reanalysis (2003-2012), a comparison with MIPAS measurements was performed. It shows that MERRA-2 underestimates ozone VMRs by up to 5 % compared to MIPAS during winter (DJF) in the Arctic stratosphere (100-1 hPa) (Wargan et al, 2017).…”
Section: Merra-2mentioning
confidence: 98%
“…The vortex initially forms because of the large meridional temperature gradient near the polar terminator during winter (Solomon, 1999). Since the northern polar vortex is generally more disturbed by planetary waves generated by the variable surface topography existing in the Northern Hemisphere (NH), SSW occur frequently in the NH every second year on average (e.g., Blume et al, 2012; Charlton & Polvani, 2007; Wang et al, 2019, among others). Examples of documented SSW events in the Southern Hemisphere (SH) are the 2002 event (Krüger et al, 2005; Varotsos, 2003; WMO, 2002) and the 2010 SSW event (de Laat & van Weele, 2011; Eswaraiah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The vertical structure of the polar vortex determines the propagation of the planetary waves (Rossby waves) that penetrate into the middle atmosphere from the troposphere [4][5][6][7][8]. At high activity of planetary waves, the polar vortex is weakening or even change the zonal wind direction from westerly to easterly, when sudden stratospheric warming (SSW) event is observed [9][10][11][12][13][14] and the destruction of the vortex is accompanied by a sharp increasing of the polar stratosphere-mesosphere temperature [1,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this paper is to investigate a planetary wave spectrum in the SSW 2018. We study the planetary wave manifestations in the stratosphere and the mesosphere over the Kharkiv region in order to continue analysis of the mesospheric carbon monoxide from the microwave radiometer measurements in Kharkiv [12]. In Section 2, the data and methods of spectral and wavelet analysis of the data are described.…”
Section: Introductionmentioning
confidence: 99%